Hematological, Biochemical, and Serological Findings in Healthy Canine Blood Donors after the Administration of CaniLeish® Vaccine - Chiara Starita; Alessandra Gavazza; George Lubas (Veterinary Medicine International)
The aim of the study was to evaluate hematological, biochemical, and serological findings in healthy canine blood donors after the administration of CaniLeish® vaccine. Twenty-seven client-owned dogs were included in the study and arranged into 3 groups according to the vaccination stage. Complete blood count (CBC) with blood smear examination, serum biochemical profile (SBP), serum protein electrophoresis (SPE), and serological tests for L. infantum were performed at different times. Additionally, in a subgroup of dogs IgA, IgM, and IgG were quantified. No statistical significance for CBC and SBP was found. In 10.7% of cases slight hyperproteinemia occurred. In SPE absolute values β-1-globulins (Group 2 and Group 2-3) and β-2-globulins (Group 3) were found modified (P<0.05). IgG values were statistically different (P<0.05) 6–8 months after the third immunisation (Group 2) and IgM and IgG values were statistically different after 2 months (Group 3). IFAT positive samples were 20.8% (Group 1), 15.0% (Group 2), and 52.8% (Group 3). Speed Leish K™ tests were always negative. The modifications found were probably attributed to the development of immune or inflammatory response due to the vaccine. Administration of CaniLeish vaccine in canine blood donors could be a safe practice and did not affect their health status.